Az antiszemitizmus definiálhatósága körüli kérdések és a zsidósággal szembeni társadalmi távolságtartás a szegedi társadalomban - Questions about Possible Definitions of Anti-Semitism and Social Ignorance of Jews in Szeged - KISS, István Márton (Belvedere Meridionale, 2013)
Studying the social presence of anti-Semitism and measuring its degree has always been accompanied by intense debates. To find answers to questions of this delicate topic from sociological point of view, we have to face a great number of challenges.The present study tries to put anti-Semitism in a terminological framework by using classical theories of sociology and other social sciences. This approach makes anti-Semitism conceivable and provides us the possibility of determining the attitudes towards Jewishness in a nuanced but practicable way. Thus, we should be able to give exact answers to questions like who can be defined as anti-Semitic and what the proportion of anti-Semitic populationis in Szeged. In order to get a factual evaluation of the results,we also have to compare the attitude towards Jews and towards other ethnic or social minorities. The representative research which served as a starting point forthis study was carried out in Szeged by the Department of Sociology of the University in 2007.